Case Report: Challenges in the surgical treatment of Marfan-associated aortic aneurysms: a literature review starting from a clinical case - Martinelli, Ombretta; Marzano, Antonio; Gonta, Valeria; Ferriero, Lucio; D’Amico, Carola; Cuozzo, Simone; Bellini, Maria Irene (Frontiers in Surgery, 2026)
Marfan syndrome (MFS) is a systemic connective tissue disease severely affecting the cardiovascular system. We present the case of a MFS 55-year-old woman who arrived at the emergency department with increasing chest pain. Over the past 25 years, this patient had undergone mitral valve annuloplasty, subsequent open surgical repair of a ruptured infrarenal abdominal aortic aneurysm followed by open surgery for a type I thoracoabdominal aortic aneurysm. She was also operated for fenestrated endovascular repair of a visceral aortic aneurysm using a ‘graft-to-graft’ approach. Upon the urgent admission, a multislice computed tomography angiography demonstrated an aortic aneurysm sac with a maximum diameter of 11.8 cm that was fed by a type IIIB endoleak, due to complete branch stent disconnection of the right renal artery (RRA) and by type IIIB/IIIC endoleaks secondary to stent fracture and disconnection in the superior mesenteric artery (SMA) and celiac trunk (CT), respectively. A common hepatic artery aneurysm (diameter of 2.29 cm) was detected, too. Under general anaesthesia a relining of both RAA and SMA was performed with Ballon-expandable Gore Viabahn and VBX stent-grafts. Subsequently, a CT stenting was successfully carried out. The bridging stents were intentionally positioned to protrude into the fenestrations to get enough overlap with the previously placed stent at the target vessel level. There were no postoperative systemic complications and the patient was discharged after 3 days under dual anti-platelet therapy. At 12 months of follow-up, complete exclusion and shrinkage of the aneurysmal sac and the patency of the stented visceral vessels are demonstrated. This complex case serves as the starting point for a literature review on current trends and perspectives in the treatment of aortic pathology related to MFS. Since MFS patients often present with aortopathy at a young age, different surgical treatments could be combined over the years to provide durable results in in protection against aortic rupture, until more effective drugs can be implemented.